2018
DOI: 10.4314/wiojms.v17i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove cover change detection in the Rufiji Delta in Tanzania

Abstract: Aims and scope: The Western Indian Ocean Journal of Marine Science provides an avenue for the wide dissemination of high quality research generated in the Western Indian Ocean (WIO) region, in particular on the sustainable use of coastal and marine resources. This is central to the goal of supporting and promoting sustainable coastal development in the region, as well as contributing to the global base of marine science. The journal publishes original research articles dealing with all aspects of marine scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Erftemeijer and Hamerlynck (2005) reported mortality in mangrove trees following severe and prolonged regional El Niño events. Monga et al (2018) reported the loss of mangrove cover (~12.4%) in the Rufiji Delta during the past…”
mentioning
confidence: 99%
“…Erftemeijer and Hamerlynck (2005) reported mortality in mangrove trees following severe and prolonged regional El Niño events. Monga et al (2018) reported the loss of mangrove cover (~12.4%) in the Rufiji Delta during the past…”
mentioning
confidence: 99%
“…This critical habitat supports diverse estuarine, coastal and marine ecosystems that are ecologically interconnected. One of the key components of the Delta is the largest mangrove area in Tanzania covering about 45,519 ha (Monga et al, 2018). Geologically, the Delta is underlain by Cretaceous and Jurassic limestones and shales, which are overlain by alluvial sand, silt, and clay deposited from the Tertiary period to the present (Mwansasu, 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Nindi et al (2014) estimated that 4,140 ha of mangroves was cleared for rice farming between 1989 and 2010. Most recently (Monga et al, 2018) reported the loss of mangroves due to rice farming at about 7,298 ha between 1991 and 2015, implying an annual loss of about 304 ha per year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations